Bridging Gaps in Pain Management: The Effectiveness of Educational Intervention for Nurses in a Teaching Hospital of Low- and Middle-Income Countries - Ali Sarfraz Siddiqui; Tabassum Zehra; Gauhar Afshan; Sara Shakil; Aliya Ahmed (Nursing Research and Practice)
Conclusion: The hybrid educational course had a significant learning impact on the knowledge of participants and their clinical practice.